A yield spread perspective on the great financial crisis: Break-point test evidence - Massimo Guidolin; Yu Man Tam (The University of Manchester, Manchester Business School, 2010)
We use a simple partial adjustment econometric framework to investigate the effects of the crisis on the dynamic properties of a number of yield spreads. We find that the crisis has caused substantial disruptions revealed by changes in the persistence of the shocks to spreads as much as by in their unconditional mean levels. Formal breakpoint tests confirm that the financial crisis has been over approximately since the Spring of 2009. The financial crisis can be conservatively dated as a August 2007 - June 2009 phenomenon, although some yield spread series seem to point out to an end of the most serious disruptions as early as in December 2008. We uncover evidence that the LSAP program implemented by the Fed in the US residential mortgage market has been effective, in the sense that the risk premia in this market have been uniquely shielded from the disruptive effects of the crisis.
Keywords: E40; E52; C23; 330; yield spreads; credit risk; liquidity risk; break-point tests; partial adjustment models